2011
DOI: 10.1128/mcb.05746-11
|View full text |Cite
|
Sign up to set email alerts
|

SCFFBXO22 Regulates Histone H3 Lysine 9 and 36 Methylation Levels by Targeting Histone Demethylase KDM4A for Ubiquitin-Mediated Proteasomal Degradation

Abstract: Reversible methylation of lysine residues has emerged as a central mechanism for epigenetic regulation and is a component of the "histone code," which engenders histones with gene regulatory information. KDM4A is a histone demethylase that targets tri-and dimethylation marks on histone H3 lysines 9 and 36. While the abundance of KDM4A oscillates in the cell cycle, little is known how this enzyme is regulated to achieve targeted effects on specific histone residues in chromatin. Here, we report that a previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 50 publications
3
84
0
Order By: Relevance
“…3A, Hom). As expected, the levels of the SCF FBXO22a substrate KDM4A increased in the purified nucleus and membrane fraction, confirming the role of hFBXO22a in regulating KDM4A levels (33).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…3A, Hom). As expected, the levels of the SCF FBXO22a substrate KDM4A increased in the purified nucleus and membrane fraction, confirming the role of hFBXO22a in regulating KDM4A levels (33).…”
Section: Resultssupporting
confidence: 57%
“…Harper and co-workers (33) reported that the SCF hFBXO22a complex ubiquitinates and regulates the steady-state levels of KDM4A, which demethylates histone H3 lysine 9 and 36 . We wondered whether hFBXO22a is also required for ubiquitination and degradation of SR by the ubiquitin-proteasomal system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations